2020
DOI: 10.1002/jmri.27084
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐Based Machine Learning for Differentiating Borderline From Malignant Epithelial Ovarian Tumors: A Multicenter Study

Abstract: BackgroundPreoperative differentiation of borderline from malignant epithelial ovarian tumors (BEOT from MEOT) can impact surgical management. MRI has improved this assessment but subjective interpretation by radiologists may lead to inconsistent results.PurposeTo develop and validate an objective MRI‐based machine‐learning (ML) assessment model for differentiating BEOT from MEOT, and compare the performance against radiologists' interpretation.Study TypeRetrospective study of eight clinical centers.Population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…To enable the VOI to be used with images from all MRI sequences, the CE‐T 1 WI, DWI, and ADC images were resampled and aligned to the same resolution, spacing, and position as the FLAIR images using the open‐source Insight Segmentation and Registration Toolkit (ITK, v. 4.7.2; https://itk.org/). 20 To standardize the MR images from all sequences, the mean value and the standard deviation of intensity in the images from each MRI volume were calculated, and each was normalized by the z‐score method, which consisted of subtracting the mean intensity and dividing by the standard deviation of intensity 21–23 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable the VOI to be used with images from all MRI sequences, the CE‐T 1 WI, DWI, and ADC images were resampled and aligned to the same resolution, spacing, and position as the FLAIR images using the open‐source Insight Segmentation and Registration Toolkit (ITK, v. 4.7.2; https://itk.org/). 20 To standardize the MR images from all sequences, the mean value and the standard deviation of intensity in the images from each MRI volume were calculated, and each was normalized by the z‐score method, which consisted of subtracting the mean intensity and dividing by the standard deviation of intensity 21–23 …”
Section: Methodsmentioning
confidence: 99%
“…20 To standardize the MR images from all sequences, the mean value and the standard deviation of intensity in the images from each MRI volume were calculated, and each was normalized by the z-score method, which consisted of subtracting the mean intensity and dividing by the standard deviation of intensity. [21][22][23] MRI feature extraction was conducted using an open-source Python package Pyradiomics (v. 2.1.2; http://www.radiomics.io/ pyradiomics.html). 24 A total of 851 image features were calculated for each MRI volume, including 14 shape-based features, 18 firstorder statistics features, 75 texture features, and 744 wavelet features.…”
Section: Radiomics Feature Extractionmentioning
confidence: 99%
“…Aramendía et al developed a CAD technique for US images that was able to discriminate between malignant and benign adnexal masses based on a texture analysis of 145 patients [ 18 ]. Jian et al and Li et al constructed an MRI-based texture analysis model to distinguish between type I and type II epithelial ovarian cancers and borderline and malignant epithelial ovarian tumors based on T2WI+DWI+ADC and CE-T1WI+T2WI [ 19 , 20 ]. Wang et al developed a CNN that distinguishes benign from malignant ovarian on T2WI, CE-T1WI, and clinical variables [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its essence is to extract high-throughput quantitative features from high-quality medical images and establish a predictive model for diagnosis and prognostic evaluation [ 19 23 ]. Previous studies have reported that radiomics has potential in the classification of ovarian cystadenomas and stratification of ovarian cysts [ 24 , 25 ]. A CT-based radiomics study has demonstrated the feasibility of predicting the risk of postoperative recurrence of advanced high-grade serous ovarian cancer [ 26 ].…”
Section: Introductionmentioning
confidence: 99%